Discourse Markers and Modal Expressions in Speakers with and without Asperger Syndrome: A Pragmatic-perceptive Approach - Muñoz, Francisco (Research in Language, 2014)
From a theoretical point of view, this paper offers a new framework for the analysis of discourse markers: a pragmatic-perceptive model that emphasizes the point of the communication process in which such particles become more relevant. Furthermore, this approach tries to give an account of the modal expressions (attenuators and intensifiers) that speakers use in oral speech. The quotients of absolute and relative frequency with regard to the use of textual, interactive and enunciative markers – focused on the message, the addressee and the addresser respectively – are compared in two samples of 20 subjects with typical development and other 20 with Asperger syndrome. The general results of this research suggest that these latter speakers display a suitable command of textual markers, whereas they overexploit the enunciative ones in conversation.